2007
DOI: 10.1111/j.1464-410x.2007.07087.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat retroperitoneal lymph‐node dissection after chemotherapy for metastatic testicular germ cell tumour

Abstract: OBJECTIVES To examine the operative findings, histopathology and clinical outcome of patients undergoing repeat retroperitoneal lymph node dissection (RPLND) after initial chemotherapy and RPLND (PC‐RPLND) for metastatic testicular germ cell tumour (GCT), as a small proportion relapse or have residual disease after incomplete resection in the lung, retrocrural or pelvic nodes, and retroperitoneum. PATIENTS AND METHODS Between September 1992 and May 2006, 359 patients had PC‐RPLND under the care of one surgeon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
(33 reference statements)
1
8
0
2
Order By: Relevance
“…Willis and colleagues, 41 from Charing Cross Hospital, reported on outcomes of 54 patients who underwent repeat RPLND following initial PC-RPLND. With a median follow-up time of 8.5 years, the investigators reported 5-and 10-year CSS of 94.2% and 91.3%, respectively.…”
Section: Clinical Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Willis and colleagues, 41 from Charing Cross Hospital, reported on outcomes of 54 patients who underwent repeat RPLND following initial PC-RPLND. With a median follow-up time of 8.5 years, the investigators reported 5-and 10-year CSS of 94.2% and 91.3%, respectively.…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…Willis and colleagues 41 reported the Charing Cross Hospital experience of 54 patients who underwent reoperative retroperitoneal surgery following PC-RPLND. The overall reported perioperative complication rate was 9% (5 cases), including a deep venous thrombosis, chest infection, lymphocele, subphrenic collection, and right ureteric injury.…”
Section: Perioperative Morbidity and Complicationsmentioning
confidence: 98%
“…However the chemotherapy had limitations because relapses tend to be chemo resistant. 5 Results of published series demonstrate that insufficient initial surgery can not compensate by chemotherapy, 7,13,14 so it makes evident that repeat surgery is the last chance of cure for the patients. Completeness and adequacy of retroperitoneal resection is a independent predictor of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, a previous series reported retroaortic and/or retrocaval recurrence in approximately half of patients undergoing reoperative RPLND. 22 Although the optimal template that offers the greatest balance between oncologic control and minimization of morbidity in the setting of lowvolume nodal metastasis remains controversial, the importance of sparing postganglionic sympathetic nerves for preservation of ejaculatory function is not. Depending on the philosophy of the operating surgeon, reduction of the surgical template in early-stage disease allows for nerve sparing through the exclusion of dissection around the contralateral postganglionic nerve fibers in early-stage patients.…”
Section: Patient Selection For Nerve-sparing Techniquesmentioning
confidence: 99%